What Doesn’t Kill You Makes You More Engaged: Rethinking the Link between Organizational Hardship and Organizational Commitment - Onyemah, Vincent (My University, 2019)
Research has consistently shown that organizational hardship (e.g., role ambiguity and conflict, work overload, organizational injustice) has a negative effect on organizational commitment. However, we posit that receiving help when combatting hardship can reverse that effect. More specifically, employees who face hardship, but receive supervisory support to oppose it, are even more engaged than employees who do not face hardship. These ideas are confirmed by empirical tests on a multinational sample of 2,742 salespeople who participated in a survey, and on a sample of 45 business students who participated in a vignette experiment.